Phase II study of computed tomography-guided 125I-seed implantation plus chemotherapy for locally recurrent rectal cancer. Issue 2 (February 2016) - Shi, Liangrong; Li, Xiaodong; Pei, Honglei; Zhao, Jiemin; Qiang, Weiguang; Wang, Jin; Xu, Bin; Chen, Lujun; Wu, Jun; Ji, Mei; Lu, Qicheng; Li, Zhong; et al.
Abstract: Background and purpose: This trial evaluated the efficacy and safety of CT guided 125 I-seed implantation (CTII) plus chemotherapy with fluorouracil, leucovorin, and irinotecan (FOLFIRI) compared with FOLFIRI alone as second-line treatment for locally recurrent rectal cancer (LRRC). Material and methods: Patients with LRRC who received one prior chemotherapy regimen were enrolled and divided randomly assigned to FOLFORI alone (Arm A) and FOLFORI plus CTII (Arm B). The primary endpoint was local control time (LCT). Overall survival (OS) and treatment related adverse events (TRAEs) were also observed. Results: Fifty-seven patients were enrolled from October 2008 and December 2014. Twenty-seven were assigned into Arm A and 30 into Arm B. The overall response rate of locally recurrent tumor was improved to 100% in Arm B versus 29.6% in Arm A ( P  < 0.001). A significant longer LCT was observed in Arm A ( P <  0.001); median LCT was 12 months in Arm B versus 4 months in Arm A. A borderline significant improvement in OS was also observed in Arm B ( P =  0.0464); median OS was 25 months in Arm B versus 19 months in Arm A. For patients without distant metastases, median OS was 37 months in Arm B versus 21 months in Arm A ( P  = 0.0101). For patients with (neo)adjuvant radiotherapy (ART), a longer LCT and OS were also found in Arm B ( P <  0.001 and P =  0.0217, respectively). TRAEs were not serious generally. There was no statistically significant difference in treatment related toxicity between Arm A and B both for all patients and patients receiving ART. Conclusions: CTII plus FOLFIRI improves the LCT with tolerable toxicities as a second-line treatment in patients with local recurrent rectal cancer, and is helpful to prolong the OS, particularly in patients without distant metastases or with a history of radiotherapy.